Analisis Kelemahan Sistem Akuntansi Penjualan dan Penerimaan Kas dalam Upaya Peningkatan Pengendalian Inrenal (PT. Ecostar Bintang Utama) - Raehanun, Raehanun; Animah, Animah; Nungki Karatikasari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Accounting information systems (AIS) have an important role for companies, because accounting information systems together with other information systems provide information needed by management as a basis for decision making. One part of the accounting information system is the sales accounting system and cash receipts accounting system. The sales accounting system influences internal control. This research aims to analyze the implementation of the sales and cash receipts accounting system in an effort to improve internal control at PT. Ecostar Bintang Utama. The research method used in this research is descriptive qualitative with a phenomenological approach. The data collection technique is in the form of observation consisting of in-depth interviews and documentation. The results of this research show that the sales and cash receipts accounting system is quite effective, the supporting documents and accounting records used are also effective, but the data presentation often experiences errors because the recording process is still done manually using only computer applications and not using a special system.